Functional bandage for ankle sprains. Recommendations for nursing - Mª Isabel Arcos Cirauqui; Barda Ochoa Alfaro; Mª Teresa Sesma Sánchez; José Usan Villanueva; Ana Gil Casado; Fernando Pérez Pejenaute (Fundación para el Desarrollo de la Enfermería, 2011)
Three quarters of ankle injuries are diagnosed as sprains. For the most part sprains are caused by a forced inversion movement with involvement of the lateral collateral ligament (LCL). One of the recommended guidelines is immobilization by taping. The aim of this article is to unify the recommendations for nursing, on taping in the treatment of ankle sprains. The methodology used was a literature review, analyzing the information found in books and journals in hospital libraries and nursing databases on the Internet. The main results are a set of guidelines for the most accurate and therapeutic taping.